Role of laparoscopy in ureteropelvic junction obstruction with concomitant pathology: a case series study - Fahmy, Omar; El-Fayoumi, Abdel Rahman; Gakis, Georgios; Amend, Bastian; Mohd Ghani @ Mamat, Khairul Asri; Stenzl, Arnulf; Schwentner, Christian (Polish Urological Association, 2015)
INTRODUCTION: Laparoscopic pyeloplasty is considered a standard treatment for ureteropelvic junction obstruction (UPJO). However, the presence of another pathology makes it a more challenging operation and guides the surgeon towards open conversion. In this study, we present our experience in difficult pyeloplasty cases managed by laparoscopy.